Exploring Critical Literacy in EFL Students’ Academic Writing: A Qualitative Study - Muhammad Fahri Jaya Sudding; Geminastiti Sakkir; Musdalifah Musdalifah (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This study aims to explore how critical literacy is manifested in EFL students’ academic writing through a discourse-oriented analysis. Employing a qualitative research design, the study analyzes 10–15 student essays collected from an undergraduate Introduction to Applied Linguistics course. The data were examined using a combination of thematic analysis and discourse analysis, focusing on key features such as argumentation, use of evidence, evaluation, writer positioning, and linguistic resources. The findings reveal that while students demonstrate familiarity with discourse analysis frameworks, their writing is predominantly descriptive rather than analytical. Students tend to identify linguistic features without critically engaging with their underlying meanings and ideological implications. In addition, the analysis shows limited critical evaluation, weak integration of supporting evidence, and minimal writer positioning. These patterns indicate that students possess procedural knowledge of discourse analysis but have not yet developed sufficient critical literacy in academic writing. The study highlights a gap between students’ theoretical understanding and their ability to apply critical thinking in writing. It suggests that EFL instruction should place greater emphasis on developing critical literacy by encouraging deeper analysis, stronger argumentation, and a more explicit authorial voice. This study contributes to the field of English language education by providing insights into how critical literacy can be better integrated into academic writing practices.